2021
DOI: 10.1007/s10753-021-01593-x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Neuropathic Pain and Attenuation of Neuroinflammation Responses by Tetrahydropalmatine Through the p38MAPK/NF-κB/iNOS Signaling Pathways in Animal and Cellular Models

Abstract: Abstract— Neuropathic pain (NP) treatment remains a challenge because the pathomechanism is not yet fully understood. Because of low treatment efficacy, there is an important unmet need in neuropathic pain patients, and the development of a more effective pharmacotherapy is urgently required. Neuroinflammation induced by oxidative stress-mediated activation of nuclear factor-kappa B (NF-κB) plays an important role in NP. In this study, we aimed to investigate the protective properties of tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Similar to previous reports [ 32 , 33 ], we used LPS to establish the in vitro neuropathic pain condition, and compared the effect of LPS on astrocytes with the effect of H 2 O 2 , a widely used inducer of cell senescence [ 34 ]. In the astrocyte cultures, the proportion of cells that robustly expressed SA β-Gal was increased after treatment with either LPS ( P Veh versus LPS = 0.005) or H 2 O 2 ( P Veh versus H2O2 = 0.003), when compared with the control (Con) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to previous reports [ 32 , 33 ], we used LPS to establish the in vitro neuropathic pain condition, and compared the effect of LPS on astrocytes with the effect of H 2 O 2 , a widely used inducer of cell senescence [ 34 ]. In the astrocyte cultures, the proportion of cells that robustly expressed SA β-Gal was increased after treatment with either LPS ( P Veh versus LPS = 0.005) or H 2 O 2 ( P Veh versus H2O2 = 0.003), when compared with the control (Con) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 NF-κB, a crucial proinflammatory mediator regulator, is essential for neuropathic pain following peripheral nerve injury. 24,25 Previous research has indicated the specific regulatory role of PTP1B in NF-κB activation in various diseases. [26][27][28] Several studies have shown that ER stress contributes to neuroinflammation via the regulation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB, a crucial proinflammatory mediator regulator, is essential for neuropathic pain following peripheral nerve injury 24,25 . Previous research has indicated the specific regulatory role of PTP1B in NF‐κB activation in various diseases 26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites of NO can generate nitroso salts, leading to oxidative reduction metabolic disorders [167]. iNOS has been detected in nerve damage caused by various factors and is closely associated with neuroinflammation and neuropathic pain [168]. The expression of iNOS has also been found in diverse central nervous system diseases, such as Alzheimer's disease, Parkinson's disease, ischemic brain injury, and traumatic brain injury [169][170][171][172].…”
Section: Inos/no•mentioning
confidence: 99%